Mean-deviational versus incremental models in adaptive control - Latawiec, Krzysztof J. (Zielona Góra: Uniwersytet Zielonogórski)
Mean-deviational and incremental formulations of the familiar adaptive control algorithms, incorporating the recursive 1S estimator coupled with different optimal single-step controllers, are extensively examined when controlling various complex SISO plants governed by the ARMAX model. In the conclusive recommendations based on a number of simulation runs, we emphasize that the mean-deviational controllers can surpass the incremental ones with respect to robustness which is the most important requirement for adaptive controllers.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka